2010
DOI: 10.2298/avb1001003k
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of hamster bone marrow haematopoietic stem and progenitor cells

Abstract: Hamster, a hibernating animal, is an important experimental model in research on the influence of hypothermia on different physiological processes. A simple procedure for cultivation and identification of hamster hematopoetic stem cells (HSC) and hematopoetic progenitor cells (HPC) is a premise for a successful investigation upon hypothermia effects on hematopoiesis. The aim of this work was to evaluate the utilization of commercially available methylcellulose media (MC) and recombinant mouse and human cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…It was observed that these bands are present but have low intensities indicating small amount of the ZnO phase in this sample. This conclusion is in good agreement with the results from XRD analysis of the ZnAl-LDH sample where the presence of a crystalline ZnO phase dispersed over the brucite-like layers was detected [25]. ZnO phase presence is of great importance due to the fact that this phase has been reported to highly contribute to the photocatalytic activity in the sunlight region [17,46].…”
Section: Structural Properties Of the Prepared Samplessupporting
confidence: 90%
See 4 more Smart Citations
“…It was observed that these bands are present but have low intensities indicating small amount of the ZnO phase in this sample. This conclusion is in good agreement with the results from XRD analysis of the ZnAl-LDH sample where the presence of a crystalline ZnO phase dispersed over the brucite-like layers was detected [25]. ZnO phase presence is of great importance due to the fact that this phase has been reported to highly contribute to the photocatalytic activity in the sunlight region [17,46].…”
Section: Structural Properties Of the Prepared Samplessupporting
confidence: 90%
“…This FTIR spectrum reveals also absorption peaks at 696 and 467 cm À1 that can be attributed to the stretching mode of Al-O in an octahedral coordination state suggesting the transformation of the crystal phase to spinel Al 2 O 4 [42]. These assumptions are verified by previous XRD analysis of this calcined sample where the collapse of the layered structure after calcination was confirmed leading to the zincite, ZnO phase and the spinel phase (ZnAl 2 O 4 ) [25].…”
Section: Structural Properties Of the Prepared Samplessupporting
confidence: 80%
See 3 more Smart Citations